Structure Design of Powerless Exoskeleton based on Passive Walking Principle - Gang Li; Wei Chen; Zhendong Song (Jixie chuandong)
Based on the principle of passive walking， a passive two-bar walking model is established， the system dynamics equation is derived and the numerical solution is carried out. On this basis， four energy conversion modules and passive assistant power joints are designed. Combining ergonomics， a powerless exoskeleton structure is designed and kinematics simulation is carried out. Using the theoretical research results， a principle prototype is processed， and the related tests and experiments are carried out.